2018
DOI: 10.1007/s11302-018-9610-y
|View full text |Cite
|
Sign up to set email alerts
|

Loss of P2X7 receptor function dampens whole body energy expenditure and fatty acid oxidation

Abstract: The established role of ATP-responsive P2X7 receptor in inflammatory, neurodegenerative, and immune diseases is now expanding to include several aspects of metabolic dysregulation. Indeed, P2X7 receptors are involved in β cell function, insulin secretion, and liability to diabetes, and loss of P2X7 function may increase the risk of hepatic steatosis and disrupt adipogenesis. Recently, body weight gain, abnormal lipid accumulation, adipocyte hyperplasia, increased fat mass, and ectopic fat distribution have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 39 publications
4
26
0
Order By: Relevance
“…To investigate the role of P2X7 activation in the regulation of energy homeostasis, we have assessed the metabolic rate and the respiratory quotient of C57BL/6J mice treated once a day for 7 consecutive days with vehicle (PBS) or the best selective and specific available P2X7 agonist BzATP, by means of continuous IC analysis during the last 48 h of treatment in standard nutritional conditions (Figure 1A). To overcome sex-mixed results with low reproducibility, we have used only the female gender because of previously reported data (Giacovazzo et al, 2018). Our results indicate that BzATP at the concentration of 1 mg/Kg (i.e., within a range demonstrated to be effective in rodents (Gubert et al, 2016), shows quick absorption without accumulation in the peritoneal space.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the role of P2X7 activation in the regulation of energy homeostasis, we have assessed the metabolic rate and the respiratory quotient of C57BL/6J mice treated once a day for 7 consecutive days with vehicle (PBS) or the best selective and specific available P2X7 agonist BzATP, by means of continuous IC analysis during the last 48 h of treatment in standard nutritional conditions (Figure 1A). To overcome sex-mixed results with low reproducibility, we have used only the female gender because of previously reported data (Giacovazzo et al, 2018). Our results indicate that BzATP at the concentration of 1 mg/Kg (i.e., within a range demonstrated to be effective in rodents (Gubert et al, 2016), shows quick absorption without accumulation in the peritoneal space.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work, we have demonstrated that genetic depletion and, to a lesser extent, also pharmacological inhibition of P2X7 elicits a pronounced decrease of the whole body EE and a significant increase of the RER, thus indicating a prevalent increase of carbohydrate oxidation. The relative sparing of fatty acids storage and concomitant defective energy homeostasis were also associated to body weight gain (Giacovazzo et al, 2018). Given the increasing importance of P2X7 in the regulation of cellular energy metabolism, either during physiological or tumor conditions (Amoroso et al, 2012; Savio et al, 2018), in the present work we have investigated by IC the effects of P2X7 activation in mice that underwent 7-days treatment with the best available selective and specific P2X7 agonist BzATP.…”
Section: Introductionmentioning
confidence: 99%
“…Before the first treatment, P2rx7 −/− animals had a higher body mass compared to the P2rx7 +/+ animals (Giacovazzo et al, 2018), which normalized after the 1 day ( Figure 10E).…”
Section: Subchronic Pcp Failed To Induce Working Memory Deficits In Pmentioning
confidence: 97%
“…In addition to depression, P2X7 receptor is closely related to the occurrence of diabetes and some diabetes comorbidities [64]. P2X7 receptors regulate insulin secretion by participating in pancreatic β cell function, and the abnormality of P2X7 function causes the imbalance in energy homeostasis and increases the accumulation of adipose tissues, which have potential effects on metabolic diseases [65]. P2X7 receptor knockout and P2X7 receptor inhibitor BBG can prevent diabetes induced by streptozocin [66].…”
Section: Role Of P2x7 Receptor In Dmmentioning
confidence: 99%